2016
DOI: 10.4172/2329-6836.1000228
|View full text |Cite
|
Sign up to set email alerts
|

Structure Antimutagenicity Relationship of Anthraquinones

Abstract: Naturally occurring anti-mutagenic principles present in plants, human diet and other sources have protective effects against mutagens. Anthraquinones (AQs) considered one of the major plant phenolic pigments that contain many members, have evidenced the capability for inhibiting the mutagenicity toward Salmonella typhimurium of a number of mutagens. Not only genotoxicity/carcinogenesis is caused by mutagens but also the inception and pathogenesis of several chronic degenerative diseases. The present review at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…Anthraquinones have antimutagenic and anticarcinogenic activities. In addition, emodin, chrysophanol, and rhein have inhibitory effects on benzo[α]pyrene-mediated DNA damage in the HepG2 hepatoma cell line [25]. Nevertheless, in this study, emodin, chrysophanol, and rhein showed effects that are antagonistic to endoxifen's action on MCF-7 and ZR-75-1 breast cancer cell lines.…”
Section: Discussionmentioning
confidence: 60%
“…Anthraquinones have antimutagenic and anticarcinogenic activities. In addition, emodin, chrysophanol, and rhein have inhibitory effects on benzo[α]pyrene-mediated DNA damage in the HepG2 hepatoma cell line [25]. Nevertheless, in this study, emodin, chrysophanol, and rhein showed effects that are antagonistic to endoxifen's action on MCF-7 and ZR-75-1 breast cancer cell lines.…”
Section: Discussionmentioning
confidence: 60%
“…However, when all antimutagenicity data were evaluated together, it was found that the presence of −CH 3 , and chloride (−Cl) substitutions at C1 did not always enhance the antimutagenic activity of 4‐TZD compounds (Table 2). This underlines that both the number, and the position of these groups are important for the antimutagenicity of 4‐TZDs [45] …”
Section: Resultsmentioning
confidence: 72%
“…This underlines that both the number, and the position of these groups are important for the antimutagenicity of 4-TZDs. [45] From a biological perspective, NaN 3 , NPDA, and 9-AA are direct-acting mutagens, and some of the newly synthesized 4-TZDs show significant antimutagenic activity against each of these mutagens (Table 2). The mutagenicity of NaN 3 is due to the production of an organic metabolite (L-azidoalanine) that enters the nucleus, and interacts with DNA, causing point mutations in the genome.…”
Section: Mutagenic and Antimutagenic Effects Of C1-c10mentioning
confidence: 99%
“…The increase reactive oxygen species formation is linked to the binding of the α, β‐unsaturated carbonyl functional group of the AQs to the sulfhydryl (‐SH) group of proteins, resulting to cellular stress (Guin, Das, & Mandal, ). The degree of AQs toxicity depends mostly on the type of the substituents attached to the main anthracene as slight structural changes can lead to reduce or increase toxicity (Mohammed, ).…”
Section: Resultsmentioning
confidence: 99%